Correlation between Postpartum Traditions and the Process of Uterine Involution - Nuraini, Indria (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Postpartum is a risky period for complications, wherein almost 60% of maternal deaths occur after childbirth and 50% of maternal deaths occur in the first 24 hours after childbirth. Factors that cause complications during postpartum period are anemia, personal hygiene, fatigue and childbirth history, such as prolonged labor, PROM, or traumatic labor. This study aims to determine the correlation between postpartum traditions and the process of uterine involution. This was an observational descriptive study. This study site was conducted at Private Practice Midwife Domingas . The population in this study were all women in postpartum Days 3-10. The samples were chosen with Total Sampling Technique. Data were analyzed using Chi Square test. The results showed that 14 respondents (36,8%) respondents did not practice postpartum traditions. The result of data analysis obtained (ρ=0.744). It can be concluded that there was no correlation between Postpartum Traditions and Uterine Involution